Peran Pendidikan Kewarganegaraan dalam Menumbuhkan Kesadaran Multikulturaisme di Sekolah Dasar - Rania Juliana Kamal; Dinie Anggraeni Dewi; Tuti Istianti (Ideguru: Jurnal Karya Ilmiah Guru, 2025)
This study aims to explore the role of Civic Education in fostering multicultural awareness among elementary school students. The background of this research is rooted in the urgency of strengthening tolerance, empathy, and respect for diversity from an early age, particularly within the context of Indonesia’s pluralistic society characterized by ethnic, religious, cultural, and social diversity. The study employed a descriptive qualitative approach, using observation, in-depth interviews, and document analysis as data collection techniques. The research was conducted in a multicultural elementary school. The participants consisted of three Civic Education teachers and fifteen students from grades IV to VI representing diverse ethnic and religious backgrounds. The findings indicate that participatory and contextual learning plays a significant role in developing students’ multicultural awareness. The integration of local values and diversity principles into lesson plans, along with learning activities that encourage intercultural dialogue, reflective discussions, and contextual experiences, effectively promotes attitudes of tolerance, empathy, and mutual respect among students. Teachers play a crucial role as facilitators in creating spaces for dialogue, guiding students’ personal reflection, and internalizing values of diversity in everyday school life. However, the effectiveness of multicultural education implementation through Civic Education is influenced by several supporting factors, including institutional support from schools, parental involvement, and the availability of continuous teacher training. This study contributes to the development of a locally based multicultural education model that can be replicated in other elementary school contexts in Indonesia. Overall, Civic Education is proven to have a tangible contribution to the formation of sustainable and collaborative multicultural awareness among elementary school students.